Intracranial Abnormalities of Infantile Hemangiomas in the Head and Neck Regions: A Retrospective MRI Study - Ying Gao; Xiao-Li Yi (Wolters Kluwer Health, 2020)
Abstract. Objective:. Few reports have described intracranial hemangiomas and structural brain and/or arterial anomalies in patients with infantile hemangiomas. This study was performed to examine the magnetic resonance imaging findings of intracranial abnormalities in a group of infants with hemangiomas in the head and neck regions. Methods:. We reviewed our hemangioma treatment center database from January 2010 to July 2018 to assess the prevalence of intracranial abnormalities in infants with hemangiomas in the head and neck regions. Clinical and electronic magnetic resonance imaging data were also retrieved from the patients' medical charts. Results:. Of 436 patients with infantile hemangiomas in the head and neck regions, 23 (5%) had intracranial abnormalities, including 20 (23%) with segmental hemangiomas and 3 (1%) with focal hemangiomas. In total, 14 patients had intracranial hemangiomas located within the ventricle and cisterns or ipsilateral lesions involving the extradural space. Eight patients had intracranial structural abnormalities, such as cerebellar dysplasia, Dandy-Walker malformation, and hydrocephalus. Five patients had intracranial arterial anomalies, and three patients had arteriovenous malformations. Conclusions:. These findings support the hypothesis that intracranial hemangiomas are commonly associated with segmental infantile hemangiomas in the head and neck regions.